Association between Home Environment and Allergies among Children in Beijing, China. (2015) - Zhang, Jinping; Zhang, Yinping; Sundell, Jan; Qu, Fang; Li, Jianong
Abstract: To identify risk factors for allergy and their contribution in the indoor environment, a population based cross sectional study was carried on among children 1-8 years old in Beijing, China during 2010-2011. The health condition, life style and home environment of children were surveyed by questionnaires. The response rate of the questionnaire was 64.8% corresponding to the number of 5763 children. The prevalence of doctor diagnosed allergic rhinitis and pneumonia was reported to be 7.8% and 26.2% respectively. 45.3% of the parents reported symptoms of rhinitis (sneezing and blocked nose) among their children in the last 12 months and 19.5% reported dry cough in the last year. Family allergy was the strongest risk factor for doctor diagnosed pneumonia, eczema, dry cough, and rhinitis in the last year. The neighborhood environment, house type, flooring, decoration, house dampness, and family member smoking are significantly associated with most reported diseases.